KELAYAKAN LKPD BERBASIS PROBLEM BASED LEARNING PEMBELAJARAN IPAS KELAS IV SDN 36 PONTIANAK KOTA - Mayuni, Irin; Kartono, Kartono; Wiyono, Hadi (Universitas Tanjungpura, 2025)
This research aims to produce a product in the form of a Student Worksheet (LKPD) based on Problem-Based Learning (PBL) for fourth-grade Natural and Social Sciences (IPAS) at SDN 36 Pontianak Kota, which is feasible in terms of both content and design, as well as to describe students